2010
DOI: 10.3344/kjp.2010.23.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion Impar Block With Botulinum Toxin Type A for Chronic Perineal Pain -A Case Report-

Abstract: Chronic perineal pain is an often encountered problem, which produces a great degree of functional impairment and frustration to the patient and a challenge to the treating physician. The reason for this problem is that the region contains diverse anatomic structures with mixed somatic, visceral and autonomic innervations affecting bladder and bowel control and sexual function. A blockade of nociceptive and sympathetic supply to the perineal region, supplied through the ganglion impar has been shown to benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 18 publications
0
33
0
2
Order By: Relevance
“…It was found that local BTX-A injections efficiently decrease pain in patients suffering from bladder pain syndrome/ interstitial cystitis, prostatitis and pelvic-floor muscle disorder (Abbott et al, 2006., Chung et al, 2012, El-Khawand et al, 2013, Gottsch et al, 2011, Kuo, 2013, Pinto et al, 2013, Smith et al, 2004, Zermann et al, 2000. In addition, there are isolated case reports on the beneficial effect of BTX-A on non-cardiac chest pain (Maradey-Romero and Fass, 2014) and perineal pain (Lim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that local BTX-A injections efficiently decrease pain in patients suffering from bladder pain syndrome/ interstitial cystitis, prostatitis and pelvic-floor muscle disorder (Abbott et al, 2006., Chung et al, 2012, El-Khawand et al, 2013, Gottsch et al, 2011, Kuo, 2013, Pinto et al, 2013, Smith et al, 2004, Zermann et al, 2000. In addition, there are isolated case reports on the beneficial effect of BTX-A on non-cardiac chest pain (Maradey-Romero and Fass, 2014) and perineal pain (Lim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few case reports pointed toward the beneficial effect of BTX-A in non-cardiac chest pain (Maradey-Romero and Fass, 2014) and perineal pain (Lim et al, 2010). Experimentally, the antinociceptive effect of BTX-A was investigated only in cystitis (Chuang et al, 2004, Coelho et al, 2014 and prostatitis (Chuang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The indications for blockade of the ganglion impar block are listed in Table 25.8 [42][43][44][45][46] .…”
Section: Indicationsmentioning
confidence: 99%
“…Blockade of ganglion Impar is usually done by injection of local anesthetic with or without steroids [4,7,8], phenol or alcohol [3,4,9], botox [6] or cryoablation [10] through various approaches like anococcygeal [4], trans-sacrococcygeal [11][12][13], trans-coccygeal [14][15][16][17]. Latest addition to this list is a non-pharmacological technique of Conventional Radiofrequency Ablation (CRF).…”
Section: Introductionmentioning
confidence: 99%
“…Blockade of the ganglion Impar has been widely accepted intervention for the management of recalcitrant chronic perineal pain of visceral and/or sympathetic origin [4][5][6].…”
Section: Introductionmentioning
confidence: 99%